Knowledge work productivity effect on quality of knowledge work in software development process in SME - Yusoff, Mohd Zairol; Mahmuddin, Massudi; Ahmad, Mazida (2016)
Knowledge and skill are necessary to develop the capability of knowledge workers.However, there is very little understanding of what the necessary knowledge work (KW) is, and how they influence the quality of knowledge work or knowledge work productivity (KWP) in software development process, including that in small and medium-sized (SME) enterprise.The SME constitutes a major part of the economy and it has been relatively unsuccessful in developing KWP.Accordingly, this paper seeks to explore the influencing dimensions of KWP that effect on the quality of KW in SME environment.First, based on the analysis of the existing literatures, the key characteristics of KW productivity are defined.Second, the conceptual model is proposed, which explores the dimensions of the KWP and its quality. This study analyses data collected from 150 respondents (based on [1], who involve in SME in Malaysia and validates the models by using structural equation modeling (SEM).The results provide an analysis of the effect of KWP on the quality of KW and business success, and have a significant relevance for both research and practice in the SME